Amyloid fibril-UiO-66-NH2 aerogels for environmental remediation. Issue 33 (7th April 2022) - Peydayesh, Mohammad; Chen, Xiulin; Vogt, Julia; Donat, Felix; Müller, Christoph R.; Mezzenga, Raffaele
Abstract : A sustainable hybrid aerogel based on β-lactoglobulin amyloid fibril/UiO-66-NH2 is developed for environmental remediation. Abstract : A sustainable hybrid aerogel based on β-lactoglobulin amyloid fibril/UiO-66-NH2 is developed for environmental remediation. The hybrid aerogel's CO2 capture and water purification performances were investigated. The hybrid aerogel can achieve CO2 capture and possesses excellent adsorption capacities for several heavy metals, dyes, and organic solvents.